2008
DOI: 10.1093/mp/ssn002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gibberellin Receptor Mutants of Barley (Hordeum vulgare L.)

Abstract: The sequence of Gid1 (a gene for a gibberellin (GA) receptor from rice) was used to identify a putative orthologue from barley. This was expressed in E. coli, and produced a protein that was able to bind GA in vitro with both structural specificity and saturability. Its potential role in GA responses was investigated using barley mutants with reduced GA sensitivity (gse1 mutants). Sixteen different gse1 mutants each carried a unique nucleotide substitution in this sequence. In all but one case, these changes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 22 publications
0
24
0
2
Order By: Relevance
“…A GID1 bait construct was prepared by amplifying a TaGID1 sequence from wheat cDNA. The TaGID1 sequence is 95% identical to the barley (Hordeum vulgare) GA receptor, GSE1 (Chandler et al, 2008), strongly suggesting that it encodes a functional GA receptor. The prey constructs containing the domains indicated in Figure 5A were cotransformed into yeast with the TaGID1 bait, and the interactions were assessed in the absence or presence of bioactive GA 3 .…”
Section: Dwarfing Mutations In Rht-b1 Abolish the Interaction With Tamentioning
confidence: 99%
“…A GID1 bait construct was prepared by amplifying a TaGID1 sequence from wheat cDNA. The TaGID1 sequence is 95% identical to the barley (Hordeum vulgare) GA receptor, GSE1 (Chandler et al, 2008), strongly suggesting that it encodes a functional GA receptor. The prey constructs containing the domains indicated in Figure 5A were cotransformed into yeast with the TaGID1 bait, and the interactions were assessed in the absence or presence of bioactive GA 3 .…”
Section: Dwarfing Mutations In Rht-b1 Abolish the Interaction With Tamentioning
confidence: 99%
“…Other factors, represented by rice GIBBERELLIN INSENSITIVE DWARF2 (GID2) and Arabidopsis SLEEPY1 (SLY1), are F-box components of Skp1-Cullin-F box protein (SCF) E3 ubiquitin ligases responsible for targeting DELLA proteins to the proteasome for degradation (McGinnis et al, 2003;Sasaki et al, 2003). Recently, a soluble GA receptor, GID1, was identified in rice and in several other plant species Griffiths et al, 2006;Nakajima et al, 2006;Hirano et al, 2007;Aleman et al, 2008;Chandler et al, 2008). The observation that GID1 and the DELLA/TVHYNP motif of DELLA physically interact in a GA-dependent manner was first made in a yeast two-hybrid (Y2H) assay and then by x-ray crystallography of GID1 forming a complex with GA and the N-terminal portion of the DELLA protein .…”
Section: Introductionmentioning
confidence: 99%
“…2B). As argued by Chandler et al, there are two possible patterns for AC94377s binding to GID1: one is that AC94377 binds to the different site in GID1 from that GA binds to, and the other is that AC94377 shares the same binding site in GID1 as GA (Chandler et al, 2008). The results in this study showed that one amino acid in the GA binding pocket of GID1 is attributable to the selectivity of AC94377 for GID1 subtype, and this amino acid is also a key site for GA activity in Figure 5.…”
Section: Discussionmentioning
confidence: 97%
“…Upon the results that AC94377 stimulated the growth in GAdeficient mutants of barley (Hordeum vulgare; grd, GA responsive dwarf) but not in GA-receptor mutants of barley (gse1, GA sensitivity), Chandler et al suggest that AC94377 activates the GA signaling via the GA receptor (Chandler et al, 2008). However, Chandler et al argued that whether AC94377 binds to the same site on the GID1 receptor as GA is still in debate (Chandler et al, 2008). Here, we studied the activities of AC94377 in Arabidopsis and found that AC94377 regulated the plant growth and transcript levels of GA-responsive genes in the same manner as GA 4 ( Fig.…”
Section: Discussionmentioning
confidence: 99%